Processamento de queijo coalho maturado a base de leite cru caprino - Silva, Rayanna Necy Renovato da (2022)
In 2019 Brazil presented a growth of 23.7% in the sale of cheese compared to the annual average of 12.8%, surpassing the sale of UHT Milk. Cheese is a milk-derived product with good acceptance by consumers, but we emphasize that handmade cheeses are gaining recognition, as they present their own geographical identity, each one with its way of making pre-established by the cheesemakers themselves. In Brazil, there is a diversity of types of cheese, but in the Northeast region, the rennet cheese stands out, among so many characteristics present in the cheese, the organoleptic properties, such as flavor and smell, are important parameters, as they add value to the product, but during the production process, its quality may be lost. In this project, we evaluated the impacts of the use of raw milk and the ripening process, were analyzed the cheeses with the addition of 1%, 2%, and 3% of sodium, matured for 15, 30, 45, and 60 days were analyzed, after the end of the final stages of ripening, these cheeses underwent analysis of chemical-physical parameters (moisture and fat), microbiological analysis to detection possible contaminants such as Staphylococcus aureus (SA), Total Coliforms (TC), Escherichia coli (EC) and Salmonella that can harm production processes and the final product; as well as the cheeses went to sensory analysis to identify off-odors and offflavors that contribute to the loss of quality.